The last pharaohs : Egypt under the Ptolemies, 305-30 BC - Manning, Joseph Gilbert (Book collections on Project MUSE., 2010)
The history of Ptolemaic Egypt has usually been doubly isolated--separated both from the history of other Hellenistic states and from the history of ancient Egypt. The Last Pharaohs departs from previous studies by putting the Ptolemaic state firmly in the context of both Hellenistic and Egyptian history. More broadly still, J.G. Manning examines the Ptolemaic dynasty in the context of the study of authoritarian and premodern states, shifting the focus of study away from modern European nation-states and toward ancient Asian ones. By analyzing Ptolemaic reforms of Egyptian economic and legal structures, The Last Pharaohs gauges the impact of Ptolemaic rule on Egypt and the relationships that the Ptolemaic kings formed with Egyptian society. Manning argues that the Ptolemies sought to rule through--rather than over--Egyptian society. He tells how the Ptolemies, adopting a pharaonic model of governance, shaped Egyptian society and in turn were shaped by it. Neither fully Greek nor wholly Egyptian, the Ptolemaic state within its core Egyptian territory was a hybrid that departed from but did not break with Egyptian history. --From publisher's description.